Psychological Well Being Predicts Parenting Stress in Mothers of Special Needs Children: Kesejahteraan Psikologis Memprediksi Stres Parenting pada Ibu Anak dengan Kebutuhan Khusus - Ashil Rizal Achmad Yani Yani; Nurfi Laili (Academia Open, 2025)
General Background: Parenting stress constitutes a complex psychological condition arising from the physical, emotional, and mental demands of childrearing, particularly in families of children with special needs. Specific Background: Mothers of children attending special schools often serve as primary caregivers and encounter sustained caregiving burdens that may relate to personal resilience and psychological well-being. Knowledge Gap: Despite growing research on parenting stress, limited empirical evidence clarifies the relative contribution of resilience and psychological well-being among mothers of children with special needs in Indonesian special school contexts. Aims: This study examines the relationship between resilience and psychological well-being with parenting stress among mothers of children with special needs enrolled in special schools in Sidoarjo. Results: Using a quantitative correlational design with multiple regression analysis on 76 participants, the findings indicate that resilience and psychological well-being jointly account for 27% of the variance in parenting stress, with psychological well-being showing a significant negative association, whereas resilience alone is not statistically significant. Novelty: The study highlights the differential role of psychological well-being compared with resilience within a Implications: These findings underscore the importance of supporting maternal psychological well-being as a central factor associated with parenting stress in families raising children with special needs. Highlights: Psychological well-being shows a significant negative association with maternal caregiving strain. Combined predictors explain 27% of variability in maternal stress levels. Resilience alone does not reach statistical significance in the regression model. Keywords: Parenting Stress; Psychological Well Being; Resilience; Mothers; Special Needs Children